General Anesthesia Compared to Spinal Anesthesia for Patients Undergoing Lumbar Vertebral Surgery: A Meta-Analysis of Randomized Controlled Trials - De Cassai, Alessandro (J Clin Med, 2020)
Vertebral lumbar surgery can be performed under both general anesthesia (GA) and spinal anesthesia. A clear benefit from spinal anesthesia (SA) remains unproven. The aim of our meta-analysis was to compare the early analgesic efficacy and recovery after SA and GA in adult patients undergoing vertebral lumbar surgery. A systematic investigation with the following criteria was performed: adult patients undergoing vertebral lumbar surgery (P); single-shot SA (I); GA care with or without wound infiltration (C); analgesic efficacy measured as postoperative pain, intraoperative hypotension, bradycardia, length of surgery, blood loss, postoperative side effects (such as postoperative nausea/vomiting and urinary retention), overall patient and surgeon satisfaction, and length of hospital stay (O); and randomized controlled trials (S). The search was performed in Pubmed, the Cochrane Central Register of Controlled Trials, and Google Scholar up to 1 November 2020. Eleven studies were found upon this search. SA in vertebral lumbar surgery decreases postoperative pain and the analgesic requirement in the post anesthesia care unit. It is associated with a reduced incidence of postoperative nausea and vomiting and a higher patient satisfaction. It has no effect on urinary retention, intraoperative bradycardia, or hypotension. SA should be considered as a viable and efficient anesthetic technique in vertebral lumbar surgery.